A targeted analysis reveals relevant shifts in the methylation and transcription of genes responsible for bile acid homeostasis and drug metabolism in non-alcoholic fatty liver disease. (December 2016) - Schiöth, Helgi; Boström, Adrian; Murphy, Susan; Erhart, Wiebke; Hampe, Jochen; Moylan, Cynthia; Mwinyi, Jessica
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is associated with a high risk for liver cirrhosis and cancer. Recent studies demonstrate that NAFLD significantly impacts on the genome wide methylation and expression reporting top hit genes to be associated with e.g. diabetes mellitus. In a targeted analysis we specifically investigate to what extent NAFLD is associated with methylation and transcriptional changes in gene networks responsible for drug metabolism (DM) and bile acid (BA) homeostasis, which may trigger liver and system toxic events. Methods We performed a systematic analysis of 73 genes responsible for BA homeostasis and DM based on liver derived methylation and expression data from three cohort studies including 103 NAFLD and 75 non-NAFLD patients. Using multiple linear regression models, we detected methylation differences in proximity to the transcriptional start site of these genes in two NAFLD cohorts and correlated the methylation of significantly changed CpG sites to transcriptional expression in a third cohort using robust multiple linear regression approaches. Results We detected 64 genes involved in BA homeostasis and DM to be significantly differentially methylated. In 26 of these genes, methylation significantly correlated with RNA expression, detecting i.e. genes such asCYP27A1, OSTɑ, andSLC27A5 (BA homeostasis), andSLCO2B1, SLC47A1, and severalUGT andCYP genes (DM) to be NAFLD dependently modulated. Conclusions NAFLD is associated with significant shifts in the methylation of key genes responsible for BA and DM that are associated with transcriptional modulations. These findings have implications for BA composition, BA regulated metabolic pathways and for drug safety and efficacy.